Gip1 GPCR regulates two sexual-stage differentiation processes in the ascomycete Fusarium graminearum - Mingyu Ding; Wanshan Wang; Yuhua Wang; Panpan Huang; Aliang Xia; Daiying Xu; Huiquan Liu; Haitao Cui; Guanghui Wang; Jin-Rong Xu; Cong Jiang (Nature Communications)
Abstract In ascomycetes, perithecium development involves sexual differentiation processes regulated by mating-related signaling pathways and mating-type locus (MAT) transcription factors, activated by uncharacterized receptors in response to stage-specific signaling cues. Here, we show that a non-pheromone receptor, Gip1, regulates two distinct sexual differentiation processes during perithecial development in the wheat scab fungus Fusarium graminearum. Gip1 controls the formation of perithecium initials via the cAMP-PKA pathway, and regulates subsequent development, including the differentiation of peridia and ascogenous tissues, via the Gpmk1 MAPK pathway. The C-terminal tail of Gip1 is important for intracellular signaling, while its N-terminal region and extracellular loop 3 are key for ligand recognition. Interestingly, all sexual-specific spontaneous suppressors of gip1 had mutations in the FgVeA gene, encoding a component of the Velvet complex, which regulates sexual reproduction in filamentous ascomycetes. These mutations partially rescue defects in either perithecium initiation or maturation in gip1 mutants, and restore upregulation of genes important for perithecium development such as MAT1-1-2 (encoding a MAT transcription factor). Thus, Gip1 controls two early stages of sexual differentiation by activating downstream cAMP signaling and Gpmk1 pathways, which may coordinately regulate the expression of genes important for initial perithecium development via FgVeA.